Evaluation of the median nerve within the wrist during functional hand activity using ultrasonography - Langley, Alyson (2010)
Over the last 20 years, an increasing number of research studies have shown that ultrasonography can provide a valid and accurate assessment of the median nerve and the pathological changes associated with median nerve disorders. More recently ultrasonographic technology has advanced and it now allows for dynamic imaging of the nerve during physical movement of the hand. However dynamic ultrasonographic imaging is still a relatively new application as is yet to be explored to its full potential in the study of median nerve dynamics and the associated pathological changes.